Therapeutic Outcomes in High-Grade B-Cell Lymphoma, NOS: Retrospective Analysis - Karunakaran, Parathan; Selvarajan, Gangothri; Kalaiyarasi, Jayachandran Perumal; Mehra, Nikita; Sundersingh, Shirley; Dhanushkodi, Manikandan; Kesana, Sivasree; Kannan, Krishnarathinam; Ganesan, Trivadi S; Radhakrishnan, Venkatraman; Sagar, Tenali Gnana (South Asian Journal of Cancer, 2022)
The nomenclature high-grade non-Hodgkin's lymphoma was repurposed in the World Health Organization (WHO) 2016 update as high-grade B cell lymphoma (HGBL). However, among the HGBL entities HGBL, not otherwise specified (NOS) remains a poorly described entity with a lack of literature regarding its treatment and prognosis.The baseline characteristics, treatment, and outcome of HGBL, NOS cases were analyzed. Thirty HGBL, NOS patients were diagnosed between January 2017 and December 2019. Their median age was 49.3 years, and 30% had advanced IPI. The majority received R-CHOP chemotherapy, while five patients received dose-adjusted R-EPOCH. At a median follow-up of 15 months, nine patients had disease progression or relapse. EFS and OS were 22 months (12.1–31.9 months) and 37 months (29.4–44.0 months) respectively. Only NCCN-IPI ≤ 2 showed significant influence on the outcome. The results were similar to the outcomes previously reported.This study highlights the importance of NCCN-IPI in ascertaining the prognosis of HGBL, NOS. The literature review suggests that more intensive chemotherapy is ideal for HGBL, NOS. However, prospective trials are needed to prove whether the treatment of HGBL, NOS can be tailored based on NCCN-IPI.
Keywords: aggressive B cell lymphoma; DLBCL; HGBL; HGBL NOS; high-grade B cell Lymphoma